Konstruksi Sosial Remaja di Tamiang Layang pada Esoterisme Religio Magis Putri Mayang Sari - Yuel Yuel (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2020)
This study aims to examine the phenomenon of religio magis putri mayang sari among Tamiang Layang Christian adolescents. The research method used is qualitative. The technique of collecting data by means of interviews, observation and documentation. The research subjects were students of SMAN 1 Tamiang Layang, caretakers of the tombs, and parents of students. The results showed that the socio-cultural construction of the Ma'anyan community towards the Puteri Mayang Rite as a social reality is an expression of Ma'anyan appreciation of the world and transcendent values are religio magis. Then, the Ma'anyan adolescent social construction of the Princess Mayang Rite was implemented in Christian Religious Education learning through interactive, inspirational, challenging learning strategies and participant observation as well as in multicultural learning. The social construction of Ma'anyan youth towards the Princess Mayang Rite contains an understanding of religious, social values, a sense of pride in one's own culture (local culture), and tolerance obtains support from educators. The results of the study recommend that Christian Religious Education teachers support the social construction of Ma'anyan adolescents so that they are conveyed in the learning process in the classroom. Penelitian ini bertujuan untuk mengkaji fenomena religio magis putri mayang sari di kalangan remaja Kristen Tamiang Layang. Metode penelitian yang digunakan adalah kualitatif. Teknik pengumpulan data dengan wawancara, observasi, dan dokumentasi. Adapun subyek penelitian adalah siswa SMAN 1 Tamiang Layang, juru kunci makam, dan orang tua siswa. Hasil penelitian menunjukkan bahwa konstruksi sosial budaya masyarakat Ma’anyan terhadap Ritus Puteri Mayang sebagai realitas sosial adalah ungkapan penghayatan Ma’anyan tentang dunia dan nilai transenden bersifat religio magis. Kemudian, konstruksi sosial remaja Ma’anyan terhadap Ritus Puteri Mayang diimplementasikan pada pembelajaran Pendidikan Agama Kristen melalui strategi pembelajaran interaktif, inspiratif, menantang, dan observasi partisipan serta dalam pembelajaran multikultural. Konstruksi sosial remaja Ma’anyan terhadap Ritus Puteri Mayang mengandung pemahaman tentang nilai religius, sosial kemasyarakatan, ada rasa bangga terhadap kebudayaan sendiri (budaya lokal), dan toleransi memperoleh dukungan dari para pendidik. Hasil penelitian merekomendasikan agar guru Pendidikan Agama Kristen mendukung konstruksi sosial remaja Ma’anyan agar disampaikan dalam proses pembelajaran di kelas.